Kajian Biblika 1korintus 15: 1-11 Bagi Pemahaman Iman Kristen Tentang Kebangkitan Yesus Kristus - Moses Wibowo; Tony Salurante (Manna Rafflesia, 2020)
The doctrine of the resurrection of Christ is one of the foundations in Christianity. But the foundation of this faith continues to be challenged and attacked. One of the attacks came from Rudolf Bultmann, who believed that the resurrection of Jesus Christ was only a spiritual awakening and not even an objective historical reality. In the Indonesian context, there is a tradition called "Rambu Solo." This tradition believes that the slaughter of a buffalo will contribute to keeping the spirits of the dead safe. The doctrine of the resurrection in Corinth was due to a problem of misunderstanding. These situations will continue to occur in various places. Therefore, this article examines Paul's teachings in 1 Corinthians 15, especially verses 1-11 as an attempt to answer the teachings and practices of life that do not understand the work of the resurrection of Jesus Christ. The method used is the biblical exegesis of 1Corinthians 15: 1-11. It is through exegesis that the resurrection of Jesus Christ is an objective historical reality. That He did rise from physical death. The exegesis significance of 1 Corinthians 15:1-11 for Bultmann's teachings and the tradition of "Rambu Solo" indicate that the two are not biblical.